2019
DOI: 10.31964/mltj.v0i0.250
|View full text |Cite
|
Sign up to set email alerts
|

Analysis between Platelet Count and Blood Groups in Apheresis Platelet Donors with Demographic Features

Abstract: Platelet transfusion is used to prevent bleeding in patients with thrombocytopenia or platelet dysfunction. Purpose of investigating demographic characteristics of eligible volunteers as platelet donors and of demonstrating the association of platelet counts with blood groups as well as other factors. We used data of individuals who referred to a blood center in our hospital. Age, body weight, body mass index (BMI), and gender were determined, and than hemogram values such as leukocyte, hemoglobin, hematocrit,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Additionally, the effects of blood groups on thrombocyte counts have also been examined. One study found that individuals with Rh (-) blood group had lower thrombocyte counts, while another study reported that individuals with blood group O had lower thrombocyte counts compared to those with blood group A (17,18). While there is some emerging knowledge about the importance of blood groups in various hematological diseases, it is worth noting that the available literature on the effects of blood groups on ITP is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the effects of blood groups on thrombocyte counts have also been examined. One study found that individuals with Rh (-) blood group had lower thrombocyte counts, while another study reported that individuals with blood group O had lower thrombocyte counts compared to those with blood group A (17,18). While there is some emerging knowledge about the importance of blood groups in various hematological diseases, it is worth noting that the available literature on the effects of blood groups on ITP is limited.…”
Section: Introductionmentioning
confidence: 99%